Acidification and solar drying of manure-based digestate to produce improved fertilizing products. (15th June 2023) - Morey, L.; Fernández, B.; Tey, L.; Biel, C.; Robles-Aguilar, A.; Meers, E.; Soler, J.; Porta, R.; Cots, M.; Riau, V.
Abstract: The increase in energy and fertilizer consumption makes it necessary to develop sustainable alternatives for agriculture. Anaerobic digestion and digestates appeared to be suitable options. However, untreated digestates still have high water content and can increase greenhouse gas emissions during storage and land application. In this study, manure-derived digestate and solid fraction of digestate after separation were treated with a novel solar drying technology to reduce their water content, combined with acidification to reduce the gaseous emissions. The acidified digestate and acidified solid fraction of digestate recovered more nitrogen and ammonia nitrogen than their respective non-acidified products (1.5–1.3 times for TN; 14 times for TAN). Ammonia and methane emissions were reduced up to 94% and 72% respectively, compared to the non-acidified ones, while N2 O increased more than 3 times. Dried digestate and dried acidified digestate can be labeled as NPK organic fertilizer regarding the European regulation, and the dried solid fraction and the improved dried acidified solid fraction can be labeled as N or P organic fertilizer. Moreover, plant tests showed that N concentrations in fresh lettuce leaves were within the EU limit with all products in all the cases. However, zinc concentration appeared to be a limitation in some of the products as their concentration exceeded the European legal limits. Highlights: A solar drying greenhouse was used to produce organic fertilizers from digestate. Acidification reduced up to 94% and 72% emissions for NH3 and CH4 respectively. The resulting products were compared with the current fertilizer EU legislation. Phytotoxicity of the resulting organic fertilizers was tested with lettuce pot trials.